Comparable Intestinal and Hepatic First-Pass Effect of YL-IPA08 on the Bioavailability and Effective Brain Exposure, a Rapid Anti-PTSD and Anti-Depression Compound - Gao, You; Yang, Chunmiao; Wang, Lingchao; Xiang, Yanan; Zhang, Wenpeng; Li, Yunfeng; Zhuang, Xiaomei (Frontiers in Pharmacology, 2020)
YL-IPA08, exerting rapid antidepressant-like and anxiolytic-like effects on behaviors by TSPO mediation, is a novel compound that has been discovered and developed at our institute. Fit-for-purpose pharmacokinetic properties is urgently needed to be discovered as early as possible for a new compound. YL-IPA08 exhibited low bioavailability (~6%) during the preliminary pharmacokinetics study in rats after oral administration. Our aim was to determine how metabolic disposition by microsomal P450 enzymes in liver and intestine limited YL-IPA08’s bioavailability and further affected brain penetration to the target. In vitro metabolic stability and permeability studies combined with in vivo oral bioavailability, panel CYP inhibitor co-administration via different routes, and double cannulation rats were conducted to elucidate the intestinal and hepatic first-pass effect of YL-IPA08 on bioavailability. Unbound brain-to-plasma ratio (Kp,uu) in rats was achieved at steady state. Results indicated that P450-mediated elimination appeared to be important for its extensive first-pass effect with comparative contribution of gut (35%) and liver (17%), and no significant species difference was observed. The unbound concentration of YL-IPA08 in rat brain (6.5 pg/ml) was estimated based on Kp,uu (0.18) and was slightly higher than in vitro TSPO-binding activity (4.9 pg/ml). Based on the onset efficacy of YL-IPA08 toward TPSO in brain, therapeutic human plasma concentration was predicted to be ~27.2 ng/ml, which is easy to reach even with unfavorable bioavailability.